PENGARUH PRODUK DAN PROMOSI TERHADAP PEMBELIAN MIE INSTAN INDOMIE GORENG DI PASAR BARU GRESIK (Fakultas Ekonomi Universitas Gresik, 2017)
This study aims to determine the effect of product, promotion, and againstDecision to purchase Indomie Goreng Instant noodle at Pasar Baru Gresik. This ResearchIs a quantitative study using survey methods. Test value ReliabiltasEach having influence X1 (0.694), X2 (0,573) and Y (0.813) onCronbach Alpa. Research subjects used are buyers in the new Market cityGresik which amounts to 66 people. Data analysis technique using F test at level5% significance. The results showed the significance test of the coefficientDone by consulting the price of F arithmetic (9,784)> F table (3.14) on 5% significance level and in Determination test R of 0.237 or 23.7% which means Shows the strong relationship between the variables of the variations of the influence of the product andPromotion of purchase decision variables, so it can be said hubungganVariable X to Y is strong.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477681